2018
DOI: 10.1089/apc.2017.0153
|View full text |Cite
|
Sign up to set email alerts
|

The Pre-Exposure Prophylaxis-Stigma Paradox: Learning from Canada's First Wave of PrEP Users

Abstract: With the emergence of daily oral tenofovir disoproxil fumarate and emtricitabine-based pre-exposure prophylaxis (PrEP) use in Canada, questions have emerged concerning the impacts of this HIV prevention tool on gay men's social and sexual lives. We conducted small focus groups and individual qualitative interviews with 16 gay men in Toronto who were part of the ‘first wave’ of Canadian PrEP users. Participants were on PrEP for at least one year as part of a demonstration project (November 2014–June 2016). Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
83
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 30 publications
(27 reference statements)
10
83
1
4
Order By: Relevance
“…Our findings about stigma are consistent with previous research identifying stigma as an important factor influencing PrEP use (Arnold et al, 2017;Collins, McMahan, & Stekler, 2017;Franks et al, 2018;García & Harris, 2017;Grace et al, 2018;Haire, 2015;Liu et al, 2014;Taylor et al, 2014;Thomann et al, 2018;. In our and other studies, PrEP stigma is closely tied to stigma around HIV, "risky" sexual behavior, and sexual and gender identity (Franks et al, 2018;Grace et al, 2018;Haire, 2015). Just as we found, other researchers have observed that stigma can be an obstacle to PrEP use, but that PrEP is also an opportunity to expose and combat stigma around HIV and sexuality (Grace et al, 2018;Storholm et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings about stigma are consistent with previous research identifying stigma as an important factor influencing PrEP use (Arnold et al, 2017;Collins, McMahan, & Stekler, 2017;Franks et al, 2018;García & Harris, 2017;Grace et al, 2018;Haire, 2015;Liu et al, 2014;Taylor et al, 2014;Thomann et al, 2018;. In our and other studies, PrEP stigma is closely tied to stigma around HIV, "risky" sexual behavior, and sexual and gender identity (Franks et al, 2018;Grace et al, 2018;Haire, 2015). Just as we found, other researchers have observed that stigma can be an obstacle to PrEP use, but that PrEP is also an opportunity to expose and combat stigma around HIV and sexuality (Grace et al, 2018;Storholm et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…In our and other studies, PrEP stigma is closely tied to stigma around HIV, "risky" sexual behavior, and sexual and gender identity (Franks et al, 2018;Grace et al, 2018;Haire, 2015). Just as we found, other researchers have observed that stigma can be an obstacle to PrEP use, but that PrEP is also an opportunity to expose and combat stigma around HIV and sexuality (Grace et al, 2018;Storholm et al, 2017). Additionally, we noted, as did others, that PrEP users had a sense of pride around PrEP (Grace et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…8,12,13 Research among potential PrEP users identifies awareness and knowledge of PrEP, costs, side effects, PrEP stigma, beliefs about HIV, and access to health care as important factors impacting uptake of PrEP. [14][15][16][17][18][19][20][21] Findings from open-label trials and demonstration projects have been similar, [22][23][24] although research in these contexts has focused on adherence and sexual behavior changes rather than uptake. [25][26][27][28][29][30] Others have studied provider barriers to PrEP implementation, finding that provider education is an important aspect of PrEP access.…”
Section: Introductionmentioning
confidence: 99%